EVALUATION STUDY OF BOGOR MARKET BUILDING STRUCTURE DUE TO THE ADDITION OF DEAD LOAD FROM RENOVATION - Muhamad Lutfi; Subtoni Subtoni (University Muhammadiyah Jakarta, 2023)
Bogor Market building until now is still operating in serving trade and sale and purchase transactions of various kinds of community needs in Central Bogor and surrounding areas to maintain market conditions, renovations are needed, one of which will currently be carried out in Bogor market is to renew the floor tiles on the ground floor, 1st floor and 2nd floor, but, thus it is necessary to conduct a study to determine whether the structure of the building is still strong to withstand the load on it after experiencing the addition of the load, from the results of field observations obtained from the addition of the thickness of the mortar is as high as 5 cm in accordance with PPURG load weight for mortar is 21 kg / m² then obtained the addition of a load of 5 x 21 kg is 105 kg/m² with analysis using softwere Etabs obtained the maximum moment value on the beam of 204.076 KNm then the required reinforcement needs of 1315 mm², after the value of the maximum moment and the need for reinforcement obtained then compared with the moment and the need for existing reinforcement, it can be concluded that all the beams of the X-axis direction (longitudinal direction) are able to withstand the load on it, while for the Y-direction beams can not withstand the load on it, due to the additional load so that the need for reinforcement is needed more. Then the recommendations given are due to the need for reinforcement on the Y axis is not sufficient, it is recommended the addition of steel plates as a substitute for the need for reinforcement to withstand the load after renovation.